Establishment and Validation of a Liquid Chromatography-Tandem Mass Spectrometry Method for the Determination of Tigecycline in Critically Ill Patients. (29th December 2020) - Yao, Fen; Wang, Yifan; Hou, Yating; Wang, Xipei; Lan, Jinhua; Wu, Zheng; Wang, Yirong; Chen, Chunbo
Abstract : Utilizing tigecycline-d9 as an internal standard (IS), we establish and validate a simple, effective, and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the quantitative measurement of tigecycline (TGC) in patient plasma. Acetonitrile was used as a precipitant to process plasma samples by a protein precipitation method. The analyte and IS were separated on an HSS T3 (2.1 × 100 mm, 3.5 μ m) chromatographic column using isocratic program with a mobile phase comprising of 80% solvent A (water containing 0.1% formic acid (v/v) with 5 mM ammonium acetate) and 20% solvent B (acetonitrile) with a flow rate of 0.3 mL/min. The mass spectrometer, scanning in multireaction monitoring (MRM) mode and using an electrospray ion source (ESI), operated in the positive-ion mode. The ion pairs used for quantitative analysis were m / z 586.4 ⟶ 513.3 and m / z 595.5 ⟶ 514.3 for TGC and the IS, respectively. The range of the linear calibration curve obtained with this approach was 50–5000 ng/ml. Intra- and interbatch precision for TGC quantitation were less than 7.2%, and the accuracy ranged from 93.4 to 101.8%. The IS-normalized matrix effect was 87 to 104%. Due to its high precision and accuracy, this novel method allows for fast quantitation of TGC with a total analysis time of 2 min. This approach was effectively applied to study the pharmacokinetics of TGC in critically ill adult patients.